2012
DOI: 10.7314/apjcp.2012.13.7.3103
|View full text |Cite
|
Sign up to set email alerts
|

LY294002 Induces G0/G1 Cell Cycle Arrest and Apoptosis of Cancer Stem-like Cells from Human Osteosarcoma Via Down-regulation of PI3K Activity

Abstract: Asian Pacific J Cancer Prev, 13,[3103][3104][3105][3106][3107] IntroductionOsteosarcoma is the most common primary mesenchymal malignant tumor of bone tissue in human, especially in children and adolescents, which tends to metastasize early with serious outcome and is more often in the metaphyseal areas of long bone such as distal femur, proximal tibia and humerus. Long-term survival rate increases from 25% to 65% with advances in surgical techniques and chemotherapy, but this figure has no obvious improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Several studies have demonstrated that alteration of PI3K/AKT/PTEN and Wnt/ β-catenin was found in many cancers and these pathways may serve as the potential targets for cancer treatment (Gong et al, 2012;Pandurangan, 2013;Jannesari-Ladani et al, 2014;Tan et al, 2014). This is the first report of the alteration of the protein components comprising the PI3K/ AKT/PTEN and Wnt/β-catenin pathway in a hamster model of Ov-induced CCA carcinogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have demonstrated that alteration of PI3K/AKT/PTEN and Wnt/ β-catenin was found in many cancers and these pathways may serve as the potential targets for cancer treatment (Gong et al, 2012;Pandurangan, 2013;Jannesari-Ladani et al, 2014;Tan et al, 2014). This is the first report of the alteration of the protein components comprising the PI3K/ AKT/PTEN and Wnt/β-catenin pathway in a hamster model of Ov-induced CCA carcinogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…PI3K activity is known to be involved in cell cycle progression [31, 32]. Because of their differential response profile to GDC-0941 treatment, MEB-Med-8A and Daoy were chosen to assess cell cycle distribution after 48 h of drug treatment (Figure 2C, upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphatidylinositol-3-kinase (PI3K)/AKT pathway plays an important role in various cellular processes including cell growth, survival and motility (Vivanco et al, 2002;He et al, 2013;Gong et al, 2012). Recently, accumulating evidence indicated that PI3K/ Akt pathway plays a crucial role in tumorigenesis and tumor progression by promoting cell proliferation and inhibiting apoptosis.…”
Section: Down Regulation Of Pi3k/akt Pathway Induce Anoikis Of Osa Cellsmentioning
confidence: 99%